1999
DOI: 10.1177/03635465990270060301
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Neuromuscular Training on the Incidence of Knee Injury in Female Athletes

Abstract: To prospectively evaluate the effect of neuromuscular training on the incidence of knee injury in female athletes, we monitored two groups of female athletes, one trained before sports participation and the other not trained, and a group of untrained male athletes throughout the high school soccer, volleyball, and basketball seasons. Weekly reports included the number of practice and competition exposures and mechanism of injury. There were 14 serious knee injuries in the 1263 athletes tracked through the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
1,214
6
33

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,298 publications
(1,277 citation statements)
references
References 30 publications
24
1,214
6
33
Order By: Relevance
“…Still, we found no improvements in SEBT from our intervention, unlike another study where significant improvements in the posterolateral and posteromedial directions were seen in youth female football players after an 8-week neuromuscular training programme [3]. Plyometric exercises were included in other similar neuromuscular programmes [2,9,12,17,19] but not in ours, and it is more likely that an improvement in jumping or sprinting performance would have been achieved if a plyometric training component was included. However, there is no clear trend in the literature about the effect of adding plyometrics, where two of the previous studies showed improvements in jumping ability [2,12], and two reported no effects [17,19].…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Still, we found no improvements in SEBT from our intervention, unlike another study where significant improvements in the posterolateral and posteromedial directions were seen in youth female football players after an 8-week neuromuscular training programme [3]. Plyometric exercises were included in other similar neuromuscular programmes [2,9,12,17,19] but not in ours, and it is more likely that an improvement in jumping or sprinting performance would have been achieved if a plyometric training component was included. However, there is no clear trend in the literature about the effect of adding plyometrics, where two of the previous studies showed improvements in jumping ability [2,12], and two reported no effects [17,19].…”
Section: Discussioncontrasting
confidence: 78%
“…Several neuromuscular training programmes have therefore been evaluated to prevent acute knee injury, ACL injury in particular, among youth female football players [8,9,11,13,16].…”
Section: Introductionmentioning
confidence: 99%
“…Each year in the United States there are approximately 250,000 ACL injuries, or 1 in 3,000 in the general population [9,10]. Numerous theories have been proposed to explain what predisposes patients to noncontact ACL injury.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, too low values of the functional H/Q indicate an imbalance in muscle strength between the agonist and the antagonist, and may contribute to a greater risk of anterior cruciate ligament (AcL) injury. A predisposition to AcL injury may also result from decreased antagonist hamstring co-activation during extension loads, as well as knee ligamentous structures bearing most of the imposed load [15,29,30]. In particular, non-contact situations may potentially occur near the foot strike when the quadriceps are eccentrically contracting to resist flexion [31,32].…”
Section: Discussionmentioning
confidence: 99%